Surgical complications due to postnatal cytomegalovirus infection in a preterm infant with malrotation. Issue 5 (28th October 2015) - Torregrossa, Anaïs; Reinberg, Olivier; Alamo, Leonor; Sarro, Rosella; Meylan, Pascal; Roth‐Kleiner, Matthias
Abstract: We report a case of an extremely preterm infant with intestinal malrotation who contracted postnatal systemic cytomegalovirus (CMV) infection with a complicated intestinal evolution requiring repeated surgical interventions and antiviral treatment. This report is to emphasize that prolonged gastrointestinal symptoms in extremely preterm infants fed with non‐pasteurized breast milk should lead to suspicion of CMV infection. The importance of preventive measures when feeding very preterm infants with breast milk needs to be considered. Furthermore, the indications for antiviral treatment, in particular in preterm infants, need to be clarified.